Inovasi Peternakan berbasis Arduino dalam Fertilisasi Telur Guna menciptakan Ketahanan Pangan di Era Pandemi Covid 19 - Tjahjono, Budi; Gilang, Destian; Anwar, Nizirwan; Karsono, Kundang (Jurnal Fokus Elektroda : Energi Listrik, Telekomunikasi, Komputer, Elektronika dan Kendali), 2020)
Abstract --- Ferilization checking generally used the candling process. For hatching, eggs were usually put into the incubator for the hatching process. Infertile eggs was usually used for consumption purposes. There were some shortcomings in the process, namely the inefficient time and inaccuracy of human vision in distinguishing the fertile or infertile eggs. Overcome this problem by using an arduino-based pulse sensor to identify eggs based on fertile eggs. The problem analysis method uses the SWOT (Strength, Weakness, Opportunity and Thread) method The research method uses the PPDIOO method (Prepare, Plan, Design, Implement, Operate and Optimize). The research results created a tool that can detect fertilized eggs automatically, separating more effectively and efficiently.Keywords: fertilization, pulse, PPDIOO, Arduino